3D tumor spheroids as in vitro models to mimic in vivo human solid tumors resistance to therapeutic drugs. Issue 1 (27th October 2018) - Nunes, Ana S.; Barros, Andreia S.; Costa, Elisabete C.; Moreira, André F.; Correia, Ilídio J.
Abstract: Three‐dimensional cell culture models, such as spheroids, can be used in the process of the development of new anticancer agents because they are able to closely mimic the main features of human solid tumors, namely their structural organization, cellular layered assembling, hypoxia, and nutrient gradients. These properties imprint to the spheroids an anticancer therapeutics resistance profile, which is similar to that displayed by human solid tumors. In this review, an overview of the drug resistance mechanisms observed in 3D tumor spheroids is provided. Furthermore, comparisons between the therapeutics resistance profile exhibited by spheroids, and 2D cell cultures are presented. Finally, examples of the therapeutic approaches that have been developed to surpass the drug resistance mechanisms exhibited by spheroids are described. Abstract : Drug resistance phenotype acquired by the cancer cells is still the major cause of the patient's low survival rates. Spheroids in vitro models represent more closely the characteristics of the human tumors, which prompted its use in the development of new therapeutics. In this review, the structural and functional similarities between spheroids and in vivo human solid tumors are reviewed, highlighting the common drug resistance mechanisms, as well as the therapeutic approaches explored to surpass this resistance. HIGHLIGHTS: The suitability of 3D cell culture models for drug screening purposes is highlighted. Spheroids and in vivo human solid tumors structural and functional similarities are emphasized. The drug resistance mechanisms exhibited by spheroids are described. Therapeutic approaches used to surpass spheroids' drug resistance mechanisms are described.